Structural and Morphological Properties of Titanium Aluminum Nitride Coatings Produced by Triode Magnetron Sputtering (2014)
TixAl1-xN coatings were grown using the triode magnetron sputtering technique varying the bias voltage between -40 V and -150V. The influence of bias voltage on structural and morphological properties was analyzed by means of energy dispersive spectroscop